Effect of association of Fusarium solani and F. moniliforme on photosynthetic characteristics in chickpea (Cicer arietinum L.) - SNEH LATA; R.K. KHETARPAL, SANGEETA KHETARPAL*, PRAMOD KUMAR, MADAN PAL, DINESH CHAND, (Indian Phytopathology, 2009)
Chickpea plants of cv. Pusa 1108 grown in normal soil in pot culture showed symptoms of disease and revealed the presence of Fusarium solani and F. moniliforme. The infected plants were assessed for the loss in photosynthetic rate. Severity of symptoms in individual plants in pot culture was assessed on a 0 to 9 rating scale based on the percentage of foliage with yellowing or necrosis in acropetal progression (0 = 0% & 9 = dead plant). Photosynthesis rate, transpiration rate, stomatal conductance, photosynthetic capacity (Pn/iCO2 ), content of chlorophyll ‘a’, chlorophyll ‘b’, ratio chla /chlb , total chlorophyll and carotenoids decreased with the progression of disease incidence/severity. However, internal CO2 exhibited a reverse trend to photosynthesis and respiration rate initially decreased up to 4 score rating and then increased from 5 to 8 score rating.